2021
DOI: 10.1021/acs.jpclett.1c01610
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Elusive Keto and Enol Intermediates in the Photolysis of 1,3,5-Trinitro-1,3,5-Triazinane

Abstract: Enols have emerged as critical reactive intermediates in combustion processes and in fundamental molecular mass growth processes in the interstellar medium, but the elementary reaction pathways to enols in extreme environments, such as during the decomposition of molecular energetic materials, are still elusive. Here, we report on the original identification of the enol and keto isomers of oxy-s-triazine, as well as its deoxygenated derivative 1,3,5-triazine, formed in the photodecomposition processes of 1,3,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…Here, the products formed in the irradiated ices along with the reactants were sublimed by increasing the temperature of the sample to 320 K at a rate of 1 K min −1 (temperature program desorption; TPD). The subliming neutral molecules were ionized exploiting isomer-selective vacuum ultraviolet (VUV) photoionization (PI) (Supplementary Table 3) [26][27][28][29][30] . The ions formed were then mass resolved in a reflectron time-of-flight mass spectrometer (PI-ReTOF-MS).…”
Section: Resultsmentioning
confidence: 99%
“…Here, the products formed in the irradiated ices along with the reactants were sublimed by increasing the temperature of the sample to 320 K at a rate of 1 K min −1 (temperature program desorption; TPD). The subliming neutral molecules were ionized exploiting isomer-selective vacuum ultraviolet (VUV) photoionization (PI) (Supplementary Table 3) [26][27][28][29][30] . The ions formed were then mass resolved in a reflectron time-of-flight mass spectrometer (PI-ReTOF-MS).…”
Section: Resultsmentioning
confidence: 99%
“…VUV photoionization mass spectrometry has attracted increasing interest due to its simplicity and low fragmentation of organic compounds. Solvent doping could remarkably enhance the ionization efficiency. , Shu et al observed that a high concentration of CH 2 Cl 2 could efficiently protonate polar molecules such as oxygenated organics. Studying the photoionization process of CH 2 Cl 2 at different pressures and concentrations will greatly help researchers to know the initial product ions and understand the enhancement mechanism.…”
mentioning
confidence: 99%